Land resource inventory (LRI) based agro-technology transfer in delta and plains of West Bengal - Bandyopadhyay, Siladitya; Reza, Sah Kausar; Maitra, Asru Kumar (Indian Farming, 2024)
Land resource inventory (LRI) based agro-technology transfer has been employed in lower Gangetic delta and Coastal plains of West Bengal. Acid saline soils occurred in 41.6% of the study area soils with severe salinity hazards. About 44.0% of area was best suited for crop diversification, while, 19.4% area was marked marginally suitable for majority of crops. LRI based best management practices (BMP) resulted in average annual benefit to cost ratio of 2.62 and average annual net returns from crops of `1,51,495, showing beneficial impact of 63.8 and 112%, respectively with average yield gain of crops by 42.0% over the existing or conventional management practices made by the farmers previously.